PENGETAHUAN DAN SIKAP IBU TENTANG PERAWATAN INFEKSI SALURAN PERNAPASAN ATAS PADA BALITA - Pratiwi, Julia; Obar, Obar; Sania, Parida; Wijaya, Sherlita Davina (Jurnal Ilmiah Kesehatan Pernus, 2024)
Organization, overall, there are around 15 million deaths of children under five per year. There are around 20-30% of them who die from ISPA. ISPA is the cause of infant and toddler deaths in developing countries. Riskesdas (2018), the incidence of ISPA in December was 25.5%, with the highest incidence occurring in five-year-old children at 35%. According to SDKI 2017, the prevalence of ISPA is highest in children aged 24-35 months, which is 14%. The results of data collection that have been carried out at the Cianjur City Health Center in 2020 found that the most cases of ISPA occurred at 4,128 cases. The purpose of this study is to explore the relationship between mothers' knowledge and attitudes about ISPA care in toddlers in the Working Area of the Cijedil Health Center, Cianjur Regency. The descriptive research method was a cross-sectional study with a sample of 93 people. The results of the chi-square test showed a relationship between mothers' knowledge and attitudes about the treatment of ISPA in toddlers in the working area of the Ciherang Health Center, Cianjur Regency with p=0.000.